Preliminary observations on biology of a man-and cattlebiting phlebotomus major major and a cave dwelling phlebotomus stantoni under laboratory conditions - R. Polseela (2018)
© 2016, Malaysian Society for Parasitology. All rights reserved. Increasing evidence of autochtonous leishmaniasis in Thailand has raised concern to understand how transmission of leishmaniasis occurs and determine its epidemiology for disease control. However knowledge of the vectorial capacity for Leishmania has been limited by difficulties and failure of sand fly breeding in the laboratory. In this study, a colony of Phlebotomus major major and Phlebotomus stantoni were established under laboratory conditions. Both colonies were started with a single gravid female and allowed to observe for all developmental stages. We reported their biological characteristics for the first time to be a baseline data for planning vector control measures. The life cycle of P. major major and P. stantoni are commonly completed in 66 days (range 48-76 days) and 48 days (range 39-49 days), respectively. Eggs hatched within 10 days after being laid. Survival rate of entire life cycle for P. major major was 38% and 100% for P. stantoni. Our results suggest that attempts to determine biological characteristics of the sand fly species and their vector potential remain vital if special attention is given to successful colonization.